FUNGSI TARI TANDUAK DALAM UPACARA BAKAWUAH DI NAGARI LATANG KECAMATAN LUBUAK TAROK KABUPATEN SIJUNJUNG - Yosi Zullyani; Afifah Asriati; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2013)
Abstract The purpose of this research is to describe the function of Tanduak dance in Bakawuah ceremony in Nagari Latang Sub-district Lubuak Tarok, Sijunjung regency. This is descriptive qualitative research. Technique of data collection were library research, observation, interview, and documentation. Technique data analysis after collecting data were analyzed accurately and selected based the needs and problems. The research found that the function of Tanduak dance in Bakawuah ceremony in Nagari Latang, Sub-district Lubuak Tarok, Sijunjung regency is as entertainment. The entertainment function is felt by people who watch and the dancer themselves. Kata kunci: Fungsi, Tari Tanduak, upacara Bakawuah